Women have a higher risk of hospital admission associated with hyponatremia than men while using diuretics - Hendriksen, L. C.; Mouissie, M. S.; Herings, R. M. C.; van der Linden, P. D.; Visser, L. E. (Frontiers in Pharmacology, 2024)
Abstract Background: Hyponatremia is a common electrolyte disturbance and known adverse drug reaction of diuretics. Women tend to be more susceptible for diuretic associated hyponatremia. The aim of this study was to find more evidence whether women have a higher risk of diuretic associated hyponatremia than men measured at hospital admission for specific diuretic groups and whether there is a sex differ-ence in risk of severity of hyponatremia. Methods: All patients using a diuretic and admitted for any reason to Tergooi MC and Haga Teaching hospital in the Netherlands between the 1st of January 2017 and the 31st of December 2021, with recorded sodium levels at admission were included in this study. Cases were defined as patients with a sodium level <135 mmol/L, while control patients had a sodium level ≥135 mmol/L at admission. Logistic regres-sion analysis was used to calculate odds ratios (OR) with 95% CIs for women versus men and adjusted for potential confounding covariables (age, body mass index, potassium serum level, systolic and dias-tolic blood pressure, estimated glomerular filtration rate, number of diuretics, comedications and comor-bidities). Stratified analyses were conducted for specific diuretic groups (thiazides, loop diuretics and aldosterone antagonists), and adjusted for dose. Furthermore, stratified analyses were performed by severity of hyponatremia (severe:<125 mmol/L), mild:125-134 mmol/L). Results: A total of 2506 patients (50.0% women) were included, of which 516 had hyponatremia at ad-mission (20.6%, 56.2% women). Women had a statistically significantly higher risk for hyponatremia at admission than men (OR 1.37; 95% CI 1.12-1.66) and after adjustment for potential risk factors (ORadj 1.55; 95% CI 1.22-1.98). Stratified analyses showed increased odds ratios for thiazides (ORadj 1.35; 95% CI 1.00-1.83) and loop diuretics (ORadj 1.62; 95% CI 1.19-2.19) among women. Use of aldosterone an-tagonists was also increased but not statistically significant (ORadj 1.15; 95% CI 0.73-1.81). Women had a statistically higher risk to develop mild and severe hyponatremia than men (ORadj 1.36; 95% CI 1.10-1.68 and ORadj 1.96; 95%CI 1.04-3.68, respectively). Conclusion: Women have a higher risk of a hospital admission associated with hyponatremia while using diuretics than men. Further research is necessary to provide sex-specific recommendations.